Knowledge, Attitude and Practice of Self-Medication among Undergraduate Pharmacy Students in University Royal College of Medicine Perak - Nur Syafiqah Abdul Fattah; Aina Amanina Abdul Jalil; Nor Safwan Hadi Nor Afendi (Asian Journal of Medicine & Health Sciences, 2022)
Background: Pharmacy students who practise self-medication are equally exposed to its hazards like the general population. It should be opted for only in the appropriate situations and not inadvertently. Proper education regarding the safe practice of self-medication should be provided to all pharmacy students. This study aims to investigate knowledge, attitude, and practice (KAP) of self-medication among undergraduate pharmacy students in Universiti Kuala Lumpur Royal College of Medicine Perak (UniKL RCMP). Methods: A cross- sectional study involving 109 students was conducted by distributing voluntary self-administrated online questionnaire. The data obtained were expressed as frequency (n), percentage (%) and mean to determine the level of respondents’ KAP on self-medication. Chi-square test was also used to identify the association between respondents’ demographic characteristics with the level of knowledge and practice on self-medication. P-value